Unique features of long non-coding RNA biogenesis and function - Quinn, Jeffrey J.; Chang, Howard Y. (Nature reviews. Genetics, 2016)
Key Points Although long non-coding RNAs (lncRNAs) and mRNAs share many common features, several types of lncRNAs are distinguished from mRNAs by unique features of biogenesis, form and function. lncRNAs exhibit more highly specific expression patterns than mRNAs. Many lncRNAs undergo special processing events, such as backspliced circularization, 5′- and 3′-bookending by processed small nucleolar RNAs (snoRNAs), and cleavage by RNase P. lncRNAs are more enriched in the nucleus than the cytoplasm relative to mRNAs, and although cytoplasmic lncRNAs associate with the ribosome, few are productively translated. Certain classes of lncRNAs are preferentially subject to degradation by nonsense-mediated decay and the nuclear exosome, and the elongation of divergent ncRNA transcripts is co-transcriptionally terminated by premature polyadenylation. lncRNAs are uniquely capable of cis action on the genome and chromatin. This feature of lncRNAs enables such biological phenomena as gene imprinting, dosage compensation of sex chromosomes, transcriptional enhancement, chromosome looping and antisense regulation. Long non-coding RNAs (lncRNAs) are a class of RNAs with great molecular and regulatory diversity. This Review discusses how, beyond their lack of protein-coding potential, some types of lncRNAs are known to exhibit features that are distinct from mRNAs, including their transcriptional regulation, localization, processing, biological capabilities and degradation. Such properties underlie many of the key cellular functions of lncRNAs. Long non-coding RNAs (lncRNAs) are a diverse class of RNAs that engage in numerous biological processes across every branch of life. Although initially discovered as mRNA-like transcripts that do not encode proteins, recent studies have revealed features of lncRNAs that further distinguish them from mRNAs. In this Review, we describe special events in the lifetimes of lncRNAs — before, during and after transcription — and discuss how these events ultimately shape the unique characteristics and functional roles of lncRNAs.